The effects of students’ characteristics on engagement in a learning management system environment / Muhammad Fadhli Abdul Rahman, Irfan Naufal Umar and Zaridah Abdullah. - Abdul Rahman, Muhammad Fadhli; Umar, Irfan Naufal; Abdullah, Zaridah (Faculty of Communication and Media Studies, Universiti Teknologi MARA, 2017)
The objective of this study is to investigate the level of students’ characteristics which are Internet Self-efficacy (ISE) and SelfRegulated Learning (SRL) on student’s engagement towards the Learning Management System (LMS) environment. The findings of this study will help universities to have more understanding towards LMS as well as student’s characteristics and student’s engagement to ensure that the implementation of LMS in the universities is a success. In this study, a survey design method was applied using a set of questionnaires as a tool to examine the effects of students’ characteristics (ISE and SRL) on engagement in LMS environment. Descriptive and inferential statistical approaches were used to analyze the data. This study involved 101 first-year students from the School of Educational Studies (SOE) Universiti Sains Malaysia. The result revealed that the students have a high level of ISE and SRL with means score of 3.74 and 4.05 respectively. Apart from that, students’ ISE and SRL were found to be significant predictors towards student’s engagement in the LMS environment.